Assessing women entrepreneurship program (WEP) as a training tool in Malaysia / Zarina Abd Munir, Salimah Mohamed Abdul Hassan, Syamsul Samsudin and Yuslizawati Mohd Yusoff - Mohamed Abdul Hassan, Salimah; Samsudin, Syamsul; Mohd Yusoff, Yuslizawati; Abd Munir, Zarina (UPENA, 2010)
This study is essentially an investigation into the nature and acceptance of the Women Entrepreneurship Program (WEP) which aims to contribute to the area of entrepreneurship training. This study, therefore, addresses the training of entrepreneurs and reveals that education and training are crucial for the development and creation of entrepreneurs in Malaysia. More specifically, this study investigates and explores whether the training content of the WEP has any effect on women starting their own businesses. This study provides a framework and discusses the content of future entrepreneurship training programs. The findings of this empirical study could help to highlight the benefits derived by the WEP delegates and the new entrepreneurial and business skills they gained. It is shown that entrepreneurship programs can help create new businesses, grow existing ones and generate new jobs. Areas for future research are outlined and various recommendations are made to the journal of International Business and Entrepreneurship guide current and prospective entrepreneurship training program developers, providers off kids, and sponsors.